PROMOTING WRITING FOR RESEARCH: THE ‘WRITING RETREAT’ MODEL - Singh, RJ (South African Journal of Higher Education, 2016)
Research papers take a long time to write and in an academic environment where the ‘publish or perish’ clause applies, writing retreats are a way of creating time and space to write academic articles in a concentrated period of time. This article examines ways in which academics can write more articles for publication. In particular it focuses on the writing retreat as a possible model that institutions can follow in order to increase publication output without over-burdening academic staff. The aim is to examine how the writing retreat model can be used to suit the needs of individual academics. Therefore, this article argues for use of the ‘writing retreat’ model to promote writing for research. The literature reviewed suggests that this type of model is commonly at HEIs with positive impact on research output. The research conducted on writing retreats was based on the experiences of academics who attended writing retreats for various purposes. Data was collected from three sources. Data was qualitatively gathered using interviews, evaluation forms and accounts of personal experiences. The findings from the research indicated that academics and postgraduate students welcomed this model of writing for research. It was found that the respondents wrote more in a concentrated period of time; they could concentrate better without distractions; they were motivated within the group and their research progressed at a faster pace. Based on the findings, a writing retreat model is proposed. The purpose of this model is to encourage academic writing for various purposes. It is also intended to motivate writing for publication in a research environment for different groups of academics so that HEIs, and in particular HBUs, can begin to increase research activity. Finally, a writing retreat model can be used for wider purposes like encouraging excellence in writing, reading and researching.